Antibiotic sensitivity and resistant pattern of bacteria isolated from table eggs of commercial layers considering food safety issue - Islam, Mahfuzul; Sabrin, Mirza Synthia; Kabir, Md Hazzaz Bin; Aftabuzzaman, Md (Asian Journal of Medical and Biological Research, 2018)
The present study was carried out during the period of June 2016 to June 2017 to evaluate the antibiotic sensitivity and resistant pattern of bacteria isolated from table eggs of commercial layers considering food safety issue. A total of 200 egg samples (100 for egg shell surface and 100 for egg content) were collected from different retail markets of Dhaka city in sterile polythene bags in a view to prevent extraneous contamination and transported to the laboratory immediate after collection using icebox. The samples were inoculated onto nutrient broth and nutrient agar plates aerobically at 37°Cfor isolation. The isolated organisms were identified based on staining, motility, colony morphology and biochemical tests. The isolated bacteria were also subjected to characterize their antibiotic sensitivity. About 74% egg samples (148 out of 200 samples) were positive for microbial contamination. Among them 100 (100 %) samples had their shells contaminated with microbes of different genera; however, only 48 (48%) growths were observed from the egg contents. The major contaminants are Escherichia coli (34.64%), Coagulase positive Staphylococcus (24.29%), Salmonella spp. (20.71%) followed by Coagulase negative Staphylococcus (10%), Pseudomonas spp. (6.43%) and Bacillus spp. (3.93%). The isolated bacteria E. coli, Coagulase positive Staphylococcus, Salmonella spp. and Pseudomonas spp. showed their greatest sensitivity against ciprofloxacin, ceftriaxone and azithromycin whereas resistant against tetracycline, amoxicillin and ampicillin. There is potential for these antibiotic-resistant bacteria to be transferred to humans through contaminated eggs and are of public health concern from food safety point of view. Asian J. Med. Biol. Res. December 2018, 4(4): 323-329